2022
DOI: 10.3390/life12060850
|View full text |Cite
|
Sign up to set email alerts
|

Recommendations of scRNA-seq Differential Gene Expression Analysis Based on Comprehensive Benchmarking

Abstract: To guide analysts to select the right tool and parameters in differential gene expression analyses of single-cell RNA sequencing (scRNA-seq) data, we developed a novel simulator that recapitulates the data characteristics of real scRNA-seq datasets while accounting for all the relevant sources of variation in a multi-subject, multi-condition scRNA-seq experiment: the cell-to-cell variation within a subject, the variation across subjects, the variability across cell types, the mean/variance relationship of gene… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 47 publications
(91 reference statements)
0
7
0
Order By: Relevance
“…If needed, scRNASequest also offers pseudo-bulk-based differential expression (DE) analysis using DESeq2 [ 61 ], limma [ 62 ], and edgeR [ 63 ]. However, as the benchmarking study reported previously, NEBULA outperforms other methods in general [ 64 ]. Thus, the pipeline uses NEBULA to perform DE analysis by default, and the parameters for running this step are defined in the configuration file (Table 2 ).…”
Section: Methodsmentioning
confidence: 82%
“…If needed, scRNASequest also offers pseudo-bulk-based differential expression (DE) analysis using DESeq2 [ 61 ], limma [ 62 ], and edgeR [ 63 ]. However, as the benchmarking study reported previously, NEBULA outperforms other methods in general [ 64 ]. Thus, the pipeline uses NEBULA to perform DE analysis by default, and the parameters for running this step are defined in the configuration file (Table 2 ).…”
Section: Methodsmentioning
confidence: 82%
“…DEseq2 and edgeR which are based on negative binomial distribution have high precision, but relatively low sensitivity, so that some TPs are easily missed. NEBULA and glmmTMB were benchmarked to have outstanding performance for differential gene expression on simulated and real multi-subject scRNA-seq data of the 10x Genomics platform [ 64 ]. However, another reference on benchmarking methods for detecting differential states between conditions from multi-subject single-cell RNA-seq data shows the pseudo-bulk methods such as DEseq2 and edgeR performed generally best [ 65 ].…”
Section: Discussionmentioning
confidence: 99%
“…To benchmark DEGman, we considered eight popular tools, DEsingle [ 7 ], DEseq2 [ 21 ], SigEMD [ 8 ], scDD [ 3 ], edgeR [ 10 ], Monocle2 [ 5 ], glmmTMB [ 12 ] and NEBULA [ 13 ] which have been shown to have superior performance in multiple method comparisons [ 20 , 35 , 61 , 64 , 65 ]. We also compared DEGman with a new DEG finding method, singleCellHaystack [ 14 ], which uses the coordinates of all cells in a low-dimensional space produced by a dimensionality reduction methods, such as principal component analysis (PCA), t-distributed stochastic neighbor embedding (t-SNE), or uniform manifold approximation and projection(UMAP) [ 66 , 67 ].…”
Section: Methodsmentioning
confidence: 99%
“…Accordingly, numerous methods for differential expression testing have been proposed and benchmarked (Soneson and Robinson 2018;T. Wang et al 2019;Crowell et al 2020;Squair et al 2021;Gagnon et al 2022). Methods originally developed for bulk RNA-seq, such as limma-voom (Ritchie et al 2015), edgeR (Robinson, McCarthy, and Smyth 2010;McCarthy, Chen, and Smyth 2012;Y.…”
Section: Introductionmentioning
confidence: 99%
“…DE analysis, at both the bulk and single-cell level, has yielded valuable insights into the mechanisms of numerous diseases (X.-S. Wang et al 2006; Adams et al 2020; Elmentaite et al 2020) and enabled the identification of drug targets (Montoro et al 2018; van den Hurk et al 2022). Accordingly, numerous methods for differential expression testing have been proposed and benchmarked (Soneson and Robinson 2018; T. Wang et al 2019; Crowell et al 2020; Squair et al 2021; Gagnon et al 2022). Methods originally developed for bulk RNA-seq, such as limma-voom (Ritchie et al 2015), edgeR (Robinson, McCarthy, and Smyth 2010; McCarthy, Chen, and Smyth 2012; Y.…”
Section: Introductionmentioning
confidence: 99%